Primary care monitoring of HbA1c tests in type 2 diabetic patients in Northern France and impact of the successive COVID-19 pandemic containments - Dr. Julie Demoule; Dr. Paul Quindroit; Dr. Camille Frévent; Prof. Dr. Claire Collins; Prof. Dr. Emmanuel Chazard; Prof. Dr. Jean-Baptiste Beuscart; Prof. Dr. Christophe Berkhout; Dr. Matthieu Calafiore; Dr. François Quersin (Diabetes Epidemiology and Management, 2024)
Background: French health authorities recommend the testing of HbA1c every 3 to 6 months in patients with diabetes. The successive containments linked to the SARSCoV-2 pandemic may have had a profound impact on the follow-up of diabetic patients in primary care. The objective of this study was to investigate the effect of containments on the volume of HbA1c assays and on HbA1c values of type 2 diabetic patients monitored in primary care in Northern France compared to usual seasonal variations. Methods: Epidemiological study of a multicentre retrospective cohort, collecting the number and the value of HbA1c assays from type 2 diabetic patients, carried out in 73 private medical analysis laboratories in Northern France region between October 1, 2018 and October 31, 2022. Results: A total of 196,744 patients and 828,037 tests were included. The first and third containments were associated with a significant decrease in the mean number of performed HbA1c tests, the decrease in the 2nd containment did not reach significance. We observed a significant decrease in HbA1c testing during the winter holiday season and the summer months. The variations in HbA1c values were not substantial compared to seasonal variations.